Os Fundamentos da repercussão geral: as funções dos recursos aos tribunais de cúpula e o descongestionamento do STF - SOUSA, Lizandro Rodrigues de (Universidade Federal do Pará, 2023)
It is a thesis that investigates the theoretical and historical foundations that supported the new configuration of diffuse constitutionality control in the STF (Supremo Tribunal Federal), with the institution of the Repercussão Geral (RG). The methodology used required a cadence. In order to identify the foundations for the institution of the RG as a filter of admissibility of the Recurso Extraordinário appeal in Brazil, we deal with each possible foundation in a specific chapter. The first possible foundation considers the role of the vertex courts based on the description of the role of judges and of the top courts, given the current guidelines of conduct. From the observation that the process has evolved, from a means to the realization of subjective rights to an effective protection of rights through fair decisions and/or the promotion of the unity of law, the study analyzes how the process and functions of the vertex courts. Would the RG help the STF to configure itself not as a court of justice, but as a court of precedents? The second possible foundation supposes the recognition that there is a worldwide tendency to solve the phenomenon of congestion of the Vertex Courts by restricting access, in order to build them into true courts of precedents. Would RG be the Brazilian version of this trend? The third possible foundation comes from the finding of the separation of the STF from the court corresponding to the historical and political justification of its conception and the conception of the Recurso Extraordinário itself, of which the RG is a current and special requirement of admissibility. In this sense, from the Constitution of 1891 onwards, the embryonic destination of this resource to sustain the supremacy of the Constitution, the authority, validity and completeness of federal law, the nature and type of Brazilian federation, is evident. Could these scopes be pursued today with the knowledge of only a relevant part of the extraordinary appeals together with the operation of other instruments, such as the actions of concentrated constitutionality control, which did not exist in 1891? The fourth possible foundation is based on the assumptions of the model found in Mitidiero (2015) or Taruffo (2011), which distinguishes the Supreme Courts from the Superior Courts. It states that a constitutional court cannot be seen as the final source of justice in the specific case, but as a court of precedents, and that ways of selecting resources according to criteria related to the general importance of the issues raised is a fundamental requirement for that a vertex court is seen as supreme. Would RG be in line with this model? The study concludes that the RG joins a list of previous attempts, thought or implemented, to overcome the centenary crisis of the Supreme Court. That currently, the RG is inserted in a positive procedural context (repetitive appeals, collective actions...) in favor of the rationalization of the practice of the Brazilian vertex courts. And that the set of grounds exposed gave support to the implementation of the RG as a solution to the STF crisis and as a directing factor of our constitutional court towards an orderly action in pursuit of its nomophylactic, standardizing and paradigmatic functions in the field of constitutional law.